Pengaruh Stres Kerja dan Turnover Intention Terhadap Kinerja Karyawan PT.Natamas Plast - Ade Nova Cristiana; Dadan Ahmad Fadili (Peneliti.net, 2023)
Every company is required to compete and maintain the performance of its company, the high level of competition and professionalism causes an increase in pressure that will be faced by individuals in the work environment, one of which is work stress and if employees are always faced with demands and a large workload will trigger employees to intend to leave the company (turnover intention). This study intends to examine the effect of work stress and turnover intention on employee performance at PT. Natamas Plast. By using quantitative methods consisting of descriptive and verifiable analysis. To research this, scale range analysis techniques and path analysis were used with the help of Microsoft Excel and SPSS software with the main data source questionnaire distributed to PT employees. Natamas Plast has 142 employees. The results obtained, namely the correlation of work stress with turnover intention of 0.722, showed a strong correlation. In addition, it is known that there is an influence of 32.6%, which means that work stress has an influence on employee performance by 32.6%. Meanwhile, the effect of turnover intention on performance is 6.91%, which means that turnover intention has an influence on employee performance of 6.91%. Meanwhile, simultaneously work stress and turnover intention on employee performance had an influence together by 61% and the remaining 39% was influenced by other variables that were not tested.